Educational intervention on food coloring awareness among elementary students: A study in Makassar, Indonesia - Sulasmi, Sulasmi; Mulyadi , Mulyadi; Rostina, Rostina; Suryadi, Iwan; Vania, Tsarwa (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
The prevalence of unsafe food coloring in snacks consumed by elementary school children remains a public health concern, particularly in urban and rural school environments. Despite ongoing efforts, studies have inadequately addressed the role of educational interventions in improving children’s awareness regarding the consumption of harmful food additives. This study aimed to evaluate the effectiveness of an educational program in enhancing knowledge about food coloring among elementary students. A community-based educational intervention was conducted at Elementary School of Inpres Cilallang, Makassar, targeting fifth-grade students. The method employed was direct health education using pre-test and post-test assessments to measure knowledge improvement. Findings revealed a significant increase in students’ understanding of harmful food colorants in street food and the ability to identify healthier snack options post-intervention. The program demonstrates the feasibility and impact of simple, targeted health education in promoting food safety awareness among school-aged children. These results highlight the importance of integrating such interventions into public health strategies, especially in urban-rural transitional zones where food safety monitoring may be limited.